Trigonometric and orthoprojection widths of classes of periodic functions of many variables - Romanyuk, A. S.; Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We obtain exact order estimates for trigonometric and orthoprojection widths of the Besov classes B^r_p,θ and Nikol’skii classes Hr p of periodic functions of many variables in the space L_q for certain relations between the parameters p and q.